Ultrawide bandgap semiconductor h-BN for direct detection of fast neutrons - J. Li; A. Tingsuwatit; Z. Alemoush; J. Y. Lin; H. X. Jiang (APL Materials)
III-nitride wide bandgap semiconductors have contributed on the grandest scale to many technological advances in lighting, displays, and power electronics. Among III-nitrides, BN has another unique application as a solid-state neutron detector material because the isotope B-10 is among a few elements that have an unusually large interaction cross section with thermal neutrons. A record high thermal neutron detection efficiency of 60% has been achieved by B-10 enriched h-BN detectors of 100 μm in thickness in our group. However, direct detection of fast neutrons with energies above 1 MeV is highly challenging due to the extremely low interaction cross section of fast neutrons with matter. We report the successful attainment of 0.4 mm thick freestanding h-BN 4″-diameter wafers, which enabled the demonstration of h-BN fast neutron detectors capable of delivering a detection efficiency of 2.2% in response to a bare AmBe neutron source. Furthermore, it was shown that the energy information of incoming fast neutrons is retained in the neutron pulse-height spectra. A comparison of characteristics between h-BN fast and thermal neutron detectors is summarized. Neutron detectors are vital diagnostic instruments for nuclear and fusion reactor power and safety monitoring, oil field exploration, neutron imaging and therapy, as well as for plasma and material science research. With the outstanding attributes resulting from its ultrawide bandgap (UWBG), including the ability to operate at extreme conditions of high power, voltage, and temperature, the availability of h-BN UWBG semiconductor detectors with the capability of simultaneously detecting thermal and fast neutrons with high efficiencies is expected to open unprecedented applications that are not possible to attain by any other types of neutron detectors.